Low incidence of airborne SARS-CoV-2 in acute care hospital rooms with optimized ventilation. Issue 1 (1st January 2020) - Dumont-Leblond, Nathan; Veillette, Marc; Mubareka, Samira; Yip, Lily; Longtin, Yves; Jouvet, Philippe; Paquet Bolduc, Bianka; Godbout, Stéphane; Kobinger, Gary; McGeer, Allison; Mikszewski, Alex; Duchaine, Caroline
ABSTRACT: The worldwide repercussions of COVID-19 sparked important research efforts, yet the detailed contribution of aerosols in the transmission of SARS-CoV-2 has not been elucidated. In an attempt to quantify viral aerosols in the environment of infected patients, we collected 100 air samples in acute care hospital rooms hosting 22 patients over the course of nearly two months using three different air sampling protocols. Quantification by RT-qPCR (ORF1b) led to 11 positive samples from 6 patient rooms ( Ct < 40). Viral cultures were negative. No correlation was observed between particular symptoms, length of hospital stay, clinical parameters, and time since symptom onset and the detection of airborne viral RNA. Low detection rates in the hospital rooms may be attributable to the appropriate application of mitigation methods according to the risk control hierarchy, such as increased ventilation to 4.85 air changes per hour to create negative pressure rooms. Our work estimates the mean emission rate of patients and potential airborne concentration in the absence of ventilation. Additional research is needed understand aerosolization events occur, contributing factors, and how best to prevent them.